A distinctive gene expression fingerprint in mentally retarded male patients reflects disease-causing defects in the histone demethylase KDM5C - Jensen, Lars R (BioMed Central, 2010)
BACKGROUND: Mental retardation is a genetically heterogeneous disorder, as more than 90 genes for this disorder has been found on the X chromosome alone. In addition the majority of patients are non-syndromic in that they do not present with clinically recognisable features. This makes it difficult to determine the molecular cause of this disorder on the basis of the phenotype alone. Mutations in KDM5C (previously named SMCX or JARID1C), a gene that encodes a transcriptional regulator with histone demethylase activity specific for dimethylated and trimethylated H3K4, are a comparatively frequent cause of non-syndromic X-linked mental retardation (NS-XLMR). Specific transcriptional targets of KDM5C, however, are still unknown and the effects of KDM5C deficiency on gene expression have not yet been investigated. RESULTS: By whole-mount in situ hybridisation we showed that the mouse homologue of KDM5C is expressed in multiple tissues during mouse development. We present the results of gene expression profiling performed on lymphoblastoid cell lines as well as blood from patients with mutations in KDM5C. Using whole genome expression arrays and quantitative reverse transcriptase polymerase chain reaction (QRT-PCR) experiments, we identified several genes, including CMKOR1, KDM5B and KIAA0469 that were consistently deregulated in both tissues. CONCLUSIONS: Our findings shed light on the pathological mechanisms underlying mental retardation and have implications for future diagnostics of this heterogeneous disorder.